Pulsed - laser deposition of superconducting Nd1.85Ce0.15Cu4− thin films and their structural examinations - Ariando Ariando; Darminto Darminto (Jurnal Fisika dan Aplikasinya, 2005)
Thin films of electron - doped superconducting Nd1.85Ce0.15CuO4− have been deposited on (100) SrTiO3 substrates at 680 - 840◦C using pulsed - laser deposition. The deposition process was conducted in flowing oxygen with the rate of 25 ml/min and the pressure of 0.25 mbar. The in-situ post-annealing treatments in vacuum (down to 10−7 mbar) for several minutes at deposition and/or lower temperatures were given to induce superconductivity on the films. The best quality of films with Tc of about 20 K, smooth surface, nanometersizedgrains and average roughness of 3.5 nm have been produced by the growing film at 820◦C followed by annealing at 750◦C in vacuum for 5 minutes.